State of the Art on User Story Mapping and Scenarios to Specify Software Requirements - Alegretti, Andrea (2024)
Requirements engineering is vital to software development, by ensuring software products comply with clients’ needs. However, it faces significant challenges, such as failures due to deficiencies in requirements specification, accounting for up to 47% of all failures in software projects. In order to mitigate these problems, adequately capturing the user’s domain knowledge and needs through Natural Language models, such as User Story Mapping (USM) and Scenarios becomes essential. This paper presents the state of the art on these two tools for software requirements specification. First, a systematic mapping study (SMS) is conducted and this is complemented by an exploratory study based on a survey in order to collect evidence on the current state of practice on the use of the User Story Mapping and Scenarios tools for requirements specification in the software industry. The results of both studies showed that USM and Scenarios are key tools in requirements specification and that using them complementarily enhances accuracy and clarity. Their direct relationship makes it possible to efficiently structure and prioritize needs, by optimizing communication between teams and enhancing the ability of projects to be adapted to the client’s requirements, thus establishing an innovative path in requirements engineering